Phase III clinical trials: No ethics no paradigm: Ensayos clínicos fase III: Sin ética no hay paradigma - De La Cruz-Vargas, Jhony A. (2021)
The phase III clinical trial is the paradigm of experimental health research and is the boundary between standard medicine and research medicine, so much so that two or more positive clinical trials support evidence-based medicine in routine clinical practice. The therapeutic, diagnostic and preventive advances of modern medicine rest to a large extent on the proper, ethical development and with the necessary scientific rigor established at the international and national levels.